2021
DOI: 10.1097/md.0000000000027883
|View full text |Cite
|
Sign up to set email alerts
|

Scheme optimization of acupoints compatibility and influence factors of the effect

Abstract: Background: Acupuncture may be a clinically effective treatment for insomnia. We will perform a multicenter, large-scale, singleblinded, randomized controlled trial to compare the differences in the clinical efficacy between the use of singleacupoints and compatibilityacupoints in the treatment of primary insomnia.Methods/Design: A total of 333 participants will be randomly assigned to 2 acupoint treatment groups or 1 nonacupoint control group in a 1:1:1 ratio by a central stochastic system. The acupuncture gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Based on the results of our review, we found that the most used acupoints for treating CRI are GV20, SP6, and HT7. GV20-SP6-HT7 is also the most used combination of main acupoints for treating insomnia ( 72 ). Studies have shown that acupuncture at GV20 can significantly improve the expression levels of clock genes and amino acid neurotransmitters in the brain tissue of rats with insomnia, thus improving sleep ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of our review, we found that the most used acupoints for treating CRI are GV20, SP6, and HT7. GV20-SP6-HT7 is also the most used combination of main acupoints for treating insomnia ( 72 ). Studies have shown that acupuncture at GV20 can significantly improve the expression levels of clock genes and amino acid neurotransmitters in the brain tissue of rats with insomnia, thus improving sleep ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncturists mostly use their experience and the patient’s schedule to pre-determine the treatment course, with a long refractory and chronic disease duration when treating diseases, and acute conditions may need a shorter course of acupuncture. 36 OAB is a chronic disease mostly suffered by middle-aged and elderly females, and a longer treatment cycle should be developed according to TCM ideas. Hargreaves et al 37 considered that acupuncture for OAB was usually 1 session per week to achieve a course of 4–12 sessions, and acupuncture also has a continual therapeutic effect and may be more clinically relevant for long-term efficacy measurement.…”
Section: Discussionmentioning
confidence: 99%
“…HT7 is the international code of Shenmen , which is the acupoint on the Shaoyin Heart Channel of Hand (手少阴心经). In TCM theory, it has the function of promoting digestion, helping sleep and regulating visceral nerves ( 76 , 77 ). Based on TCM theory, the pathogenesis of ASD is related to the abnormal function of the heart, liver, spleen, and kidney.…”
Section: Clinical Trialsmentioning
confidence: 99%